Group cognitive-behavioral therapy for insomnia: a meta-analysis - Navarro-Bravo, Beatriz; Párraga-Martínez, Ignacio; López-Torres Hidalgo, Jesús; Andrés-Pretel, Fernando; Rabanales-Sotos, Joseba (Anales de Psicología / Annals of Psychology, 2014)
Background: insomnia is a highly prevalent disorder in the general population and in clinical practice. Although pharmacological treatment is the most widespread choice, psychological treatment appears to have longer lasting effects. The main objective of this meta-analysis was to assess the cognitive-behavioural group therapy treatment for insomnia. Method: a systematic search for cognitive-behavioural therapy clinical trials in Pubmed, PsycINFO, PsycARTICLES, Scielo, WOK, Cochrane, Scopus and Embase. 153 articles were reviewed, of which 9 met inclusion criteria for the metaanalysis. Adding up the data from all 9 trials, a total of 699 people completed the post-test phase. Results: after finishing cognitive-behavioural therapy, significant improvements regarding insomnia were found according to the Pittsburgh Sleep Quality Index and Insomnia Severity Index, sleep latency, wake after sleep onset and sleep efficiency. There were no significant improvements in total sleep time. Conclusions: the results from experimental studies on cognitive-behavioural therapy as an insomnia treatment clearly suggest a positive impact on symptoms, as assessed using both validated scales and sleep diaries.